A descriptive analysis of anglicism in Ecuadorean newspapers - Chiriboga Mansfield, Cristina (2012)
As a requisite to obtain our Bachelor‟s Degree in Teaching English as a foreign language, we carried out a conscious research and later elaboration of the final thesis, based on “A Descriptive Analysis of Anglicisms used in Ecuadorian Newspapers”. To accomplish this research, we used as variables a national newspaper, El Comercio, which is printed in Quito, but has national distribution. A local newspaper Últimas Noticias, which is printed in Quito, the capital city of Ecuador, and almost all its distribution, is centered in the province of Pichincha. And, finally, we studied the sections of a tabloid, El Extra, which is mostly distributed in the city of Quito and surrounding valleys. From each variable, we centered our research on the sections or sub variables: news, advertisements, social pages, sports and articles. Through an analytic and descriptive analysis of the anglicisms found on the mentioned sections, we made a study that led us to have a clear vision of the extended use of anglicisms in Ecuadorian newspapers, as well as the syntactic-semantic and morphological changes that English words suffered when being borrowed in Spanish. The information obtained after studying the samples chosen, is clearly stated in the Results section, which contains charts that helped us document the qualitative and quantitative characteristics - 2 - of the borrowed words and were a basic aid made for a comparative and sociological analysis of the results. To conclude our study and as extra help in our examination, we interviewed people we believed better represent and have valid opinions about the use of Anglicisms in Spanish. After the completion of this research, we concluded that there are some good borrowed words that help with expression and enriche the Spanish language, but most of the Anglicisms found in newspapers constitute exaggerations and overuse. We deem that this excess use derives from globalization, but is mainly due to the large migration of Ecuadorians to United States looking for a better standard of living.